Efficiency of traditional maize storage and control methods in rural grain granaries: a case study from Senegal - Gueye, M.; Goergen, Georg E.; Ndiaye, S.; Asiedu, E.; Wathelet, J.; Lognay, G.; Seck, D. (2013)
Maize storage and pest control method as practiced in traditional clay granaries in the Kédougou region in eastern Senegal were evaluated under rural conditions during two successive years. Three storage modes, i.e. maize cobs, winnowed and non-winnowed maize grains, were tested in seven granaries where the insecticidal plants Hyptis spicigera or H. suaveolens were either incorporated in the store structure or deposited as layers intermittently with maize. At the beginning of the storage period, all granaries were artificially infested with 7 pairs Tribolium castaneum and Sitophilus zeamais. No damage, losses or live insects were observed during 7 months of storage when maize cobs were placed between layers of H. spicigera. Compared with the control, incorporation of insecticidal plants within the granary bottom had no significant effect on the damage and loss level irrespective of the storage mode. Non-winnowed maize always suffered less damage and losses than the winnowed variant. In all granaries depredation, insect abundance and moisture content were highest toward the end of storage period between June and July.